Occurrence of Ulcerative Colitis in a Patient With Adult-Onset Still's Disease: Coincidence or Correlated - Yun Jung CHOI,; Wan-hee YOO, (Archives of Rheumatology, 2017)
A 37-year-old male patient with adult-onset Still’s disease (AOSD) developed ulcerative colitis (UC) during the course of treatment. He complained of abdominal pain, diarrhea, and frequent passage of blood-stained stool with peri-umbilical tenderness. The laboratory evaluation was significant only for a hemoglobin level of 11 g/dL. The patient underwent endoscopic and colonoscopic examination with the presumptive diagnosis of nonsteroidal anti-inflammatory drug-induced gastropathy. Unexpectedly, the colonoscopic and pathologic findings of the biopsy specimen were compatible with UC. To our knowledge, this is the first report of AOSD concurrently occurring with UC. In patients with AOSD, abdominal pain is likely to be mistaken for nonsteroidal anti-inflammatory drug-induced gastropathy. However, several studies imply the possibility of UC as an extra- articular manifestation of AOSD. Although coexistence of AOSD and inflammatory bowel disease is rare, timely diagnosis is important since this co-occurrence may aggravate this otherwise benign disease.